Ahmad Sanusi Sukabumi's Efforts in Straightening the Concept of Absolute Water Opposing the Other Pesantren Leaders | جهود الكياهي الحاج أحمد سنوسي السوكابومي في بيان حقيقة الماء المطلق تجاه رؤساء بيزانترين - Istikhori Istikhori (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2020)
This article is a concerted effort in further introducing the figure of K.H. Ahmad Sanusi from Sukabumi as one of the Indonesian scholars who has an important role in building a critical culture in studying religious texts, and also his intelligence in answering the religious issues that arise by returning the issue to the basic understanding of the Prophet's traditions proportionately, by not ignoring the statements of the scholars in other literatures that also speak in the same subject matter, in order to obtain a holistic scientific answer. Besides the historical approach, the philological approach is also another part of the writing of this paper. The historical approach is intended to see how the religious attitudes of K.H. Ahmad Sanusi in the face of the emergence of religious understanding that is not in accordance with the flow of science in solving religious problems in the 40s. By presenting scientific data in his book through philological studies, this paper seeks to see a brilliant line of thought, especially in answering claims to be able to purify (wudhu) using tea water, as well as comparison with the thoughts of other scholars in his time.